Coordinated generation and transmission expansion planning approach considering probabilistic available transfer capability. Issue 1 (May 2020) - Zhou, Ping; Kang, Peng; Chen, Ruiguo; Tian, Hao
Abstract: The available transmission capacity of the network has a great impact on the safety and reliability of the whole system. After the reform of electricity market, the grid is required to have the highest available transmission capacity (ATC) based on the existing load due to the uncertain factors. Therefore, it is necessary to consider the growing demand for available transmission capacity from the grid planning stage. Meanwhile, considering the uncertain factors have a great influence on the available transmission capacity (ATC), this paper first models the three uncertain factors and introduces the solving method of probabilistic available transfer capability, then proposes a grid expansion planning model considering the probabilistic available transmission capacity under the influence of uncertainties, which is applied to the six-node test system. Finally, the genetic algorithm is used to solve the final planning scheme. Compared with other planning schemes, this method can consider the comprehensive investment cost and the probability available transmission capacity. The case study shows that the method is effective and can achieve good results.